4 - The Contradictory and Complementary Relationship Between Student Constructive Engagement and Protest Strategies in South African Higher Education - Cele, Mlungisi (Journal of Higher Education in Africa, 2008)
Some claim that the present democratic state has made enormous progress in transforming South African society in general and higher education in particular. On the contrary, there is persistent and widening social inequality reflected in all spheres of life affecting predominantly poor, African and working class strata of society. On average, about 25 per cent of students leave higher education institu- tions annually in South Africa because they are excluded on academic and finan- cial grounds. To reduce dropout/exclusions student boycotts and protests are com- mon despite the institutionalisation of student participation (commonly referred to as ‘constructive engagement’) in higher education (HE) governance in 1997. The paper explores the dimensions of various protests and examines some of the effects of student participation in HE governance structures.